(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Support Vector Machines, Reinforcement algorithms, artificial neural networks are some of the Machine Learning Algorithms available in Medical Analysis. By using these algorithms, much of the research has been done in analysis of liver cancer for genome classification and identification of lesions. At present, Deep learning algorithms have quickly turned into a strategy for examine CT images. This article presents one of the major deep learning techniques named tensor flow technique to investigate images in scan for the task of visualization of abnormal condition of liver tumor in the context of shape and color towards disease diagnosis. We surveyed the utilization of tensor flow for classifying images, detection of objects, and detection of lesions. In this paper, we mainly concentrated on the study and working of tensor flow in image classification. Also, a summary of the present and future scope in this area has been presented in detail.